Thyroid fine needle aspiration biopsy: The effect of radiological features of nodules on cytological adequacy - Şahin, Cennet; Von Bodelschwingh, Bade (Journal of Surgery and Medicine, 2020)
Aim: Thyroid fine needle aspiration biopsy (FNAB) is an inexpensive and microinvasive procedure used in the diagnosis of thyroid nodules. However, cytology may be insufficient in up to 40% of biopsies. This study aimed to assess the effect of radiological features of thyroid nodules on cytological adequacy. Methods: The patients who underwent thyroid FNAB between 2016 and 2019 in our clinic were reviewed in this retrospective cohort study. Diagnostic adequacy rate and radiological features of nodules (size, cystic component, calcification content, echogenicity, margin feature) were noted and their relationship was investigated. Results: A total of 525 patients (77% female, 23% male; mean age 53.3 years; age range 14-87) had FNAB for 595 nodules. Mean diameter of the nodules was 20.1 mm (min: 4mm; max: 60 mm). Of the all biopsies, 25% were inadequate for diagnosis. Adequacy was significantly low in nodules containing macrocalcification (P=0.036). There was no significant relationship between adequacy and echogenicity, margin feature, solid structure or size of the nodules (P>0.05 for each). Conclusion: Some radiological features may be predictive of inadequate sampling. Nevertheless, varied extrinsic factors affect cytopathological adequacy besides radiological features. Additional techniques may be required in these nodules.